Implementasi Permainan Kolaboratif Untuk Mengontrol Sosial Emosional Selama Proses Pembelajaran Di Luar Ruangan Pada Anak Sdn 1 Kartasura - Wahyunnisa Aisy Agustini; Anniez Rachmawati Musslifah (Universitas Kristen Indonesia Toraja, 2024)
This research faced challenges in incorporating web design skills into the curriculum of SMK Istiqomah Muhammadiyah 4 Samarinda with limited resources. Through the prototype method and the Figma platform, PKL projects are used to teach students about website development. The aim is to provide relevant skills to the technology and graphic design industries. The steps include requirements analysis, prototyping, user evaluation, and user interface design for the company profile. The result is expected to be a web application that is informative, interesting, and in accordance with the needs of the vocational school Abstract.This research aims to implement collaborative games as a strategy to control social emotional development in school-aged children at SDN 1 Kartasura. School-aged children have diverse emotional characteristics, and social-emotional development is very important to shape children's personality and independence. Collaborative games were chosen as a method to stimulate children's social abilities through group activities. The initial stage of this research includes understanding the potential and challenges of social emotional development in school-aged children. Furthermore, a collaborative game was designed and implemented on September 9 2023, involving 25 grade 4 students at SDN 1 Kartasura. This activity includes game sessions, observations of social interactions, and evaluation of activity results which show that the implementation of collaborative games has a positive impact on students' social emotional development. However, research also identifies several obstacles, such as some students who still experience difficulties in socializing and controlling emotions. Therefore, further efforts are needed to maximize the potential of collaborative play in improving children's social emotional development. In conclusion, implementing collaborative games can be an effective approach to creating a positive learning environment and improving students' social emotional development at SDN 1 Kartasura. This research contributes to the understanding of social emotional development strategies in school-aged children through collaborative play.